2011
DOI: 10.1111/j.1442-2042.2011.02839.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of urinary flow studies after hypospadias repair: A systematic review

Abstract: A systematic review was performed of publications relating to the results of urinary flow studies after hypospadias repair dating back to 1978, when what appears to be the first publication on this topic was found. The literature search was performed using the key words "hypospadias" combined with "urinary flow", "urine flow", "uroflow", "uroflowmetry", and "long-term". We also reviewed the abstracts and full-length articles cited in the reference list of selected articles. Criteria for inclusion in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…7 Gonzalez and Ludwikowski previously highlighted the importance of this worrisome complication and predicted that urologists will need to treat a number of patients with this problem in the next 2 decades. 8 The incidence has been reported at 4.7% (range 0% to 19%) in the literature. 4 The condition can either be treated with urethrotomy, with dilation or conservatively but it is often unrecognized and thus underdiagnosed.…”
Section: Discussionmentioning
confidence: 96%
“…7 Gonzalez and Ludwikowski previously highlighted the importance of this worrisome complication and predicted that urologists will need to treat a number of patients with this problem in the next 2 decades. 8 The incidence has been reported at 4.7% (range 0% to 19%) in the literature. 4 The condition can either be treated with urethrotomy, with dilation or conservatively but it is often unrecognized and thus underdiagnosed.…”
Section: Discussionmentioning
confidence: 96%
“…While some studies claimed that majority of patients exhibited normal flow pattern [14][15][16], others reported an obstructed flow in a significant proportion of cases [17,18]. In a systematic review addressing the importance of uroflowmetry studies after TIP repair, 11 studies reported obstructive flow in 24.6% of patients (93 / 378) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Uroflow data are depicted in table 2. Using a nomogram for age matched children [8], the Qmax was plotted against the voided volume where 4 out of 28 cases (14.3%) had obstructed flow with a Q-max values below the 5 th percentile on the nomogram, two in each group, that is below than previously reported in the literature [19]. Qmax values in most cases were between 25 th and 50 th percentile of the nomogram while Qave values were above the 5 th percentile (Figure 3 a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Complications post hypospadias repair are well described, with approximately 20% of all comers requiring further surgery [10]. Approximately half will require a further operation within year one, 38% after year two and 5% after year three [8].…”
Section: Discussionmentioning
confidence: 99%